Comparison of electrochemical response and electric field emission characteristics of pristine La2NiO4 and La2NiO4/CNT composites: Origin of multi-functionality with theoretical penetration by density functional theory. (10th February 2021) - Karmakar, S.; Mistari, Chetan D.; Vaidyanathan, Antara; More, M.A.; Chakraborty, Brahmananda; Behera, D.
Highlights: Developed honeycomb La2 NiO4 nanostructured and its CNT blending complex for electrochemical and field emission study. La2 NiO4 /CNT exhibits better specific capacity (426 mAh g −1 ) and current density (1705 µA/cm 2 ) than pristine La2 NiO4 . Charge transfer from La2 NiO4 to CNT enhances due to interaction between d orbitals of Ni and La with 2p orbital of C. The theoretical quantum capacitance and local work function (φ) for field enhancement factor (β) have been computed. Abstract: Electrochemical performances of as-prepared La2 NiO4 and La2 NiO4 @CNT based electrode are investigated in a 1M KOH solution using a three-electrode configuration. The La2 NiO4 electrode delivers the specific capacity ( C s p ) 284 mAh g −1 at a current density 1.5 A g −1 with rate capability 74.5% at a current density 12 A g −1 and its value intensified up to 426 mAh g −1 with capability 82.1% at identical current density due to incorporation of CNT. Long-range stability and Nyquist plot ( Z ′ v s . Z ″ ) of the La2 NiO4 @CNT electrode exhibit better cyclic performances with capacity retentivity 93% after 3000 cycles and excellent charge transfer characteristics than pristine La2 NiO4 electrode (capacity retentivity 85.6%). Fowler–Nordheim tunneling in electric field emission of CNT modified La2 NiO4 exhibits superior current density ( J~ 1705 µA/cm 2 ) with inferior turn-on@1 µA/cm 2 and threshold field@10µA/cm 2 1.92 V/µm and 2.15 V/µm respectively. The enhanced electronic states near Fermi level for hybrid La2 NiO4 /CNT leading to improved conducitivity, increase mobility of electrolytic ions in the open space of CNTs and higher quantum capacitance support the improved charge storage performance. There is charge transfer from La2 NiO4 to CNT due to interaction between d orbitals of Ni and La with 2p orbital of C. Also, reduction in work function for hybrid La2 NiO4 /CNT compared to pristine La2 NiO4, introduction of defects near the boundary and improved conductivity attribute towards higher emission current observed in the experiment. Graphical abstract: Image, graphical abstract